Analysis of and Research on the Development of Lower Limb Wearable Exoskeleton - Meng Fei; Peng Xingyu; Xu Younan (Jixie chuandong)
Lower limb exoskeleton has always been a hot research direction in the field of exoskeleton development. In the research of lower limb exoskeleton, it can be divided into two driving types, including powered system drive and unpowered passive lower limb exoskeleton. In the powered system driven lower limb exoskeleton, it can be divided into rigid lower limb exoskeleton and flexible lower limb exoskeleton. The research on two different driven types of lower extremity exoskeletons is reviewed in this study. The development status, structure principle, advantages and disadvantages of the equipment are introduced, and their performance and the key technologies that need to be paid attention to in the future research are analyzed.